Studying at higher education institutions in Poland as seen by students with disabilities in the context of the geographical model of disability - Zajadacz, Alina; Kołodziejczak, Anna (Quaestiones Geographicae, 2023)
The subject addressed in the present paper is important for the current social and educational policy regarding persons with disabilities. The development of the accessible education concept should be based on the geographical model of disability, whose main principle is to focus on the varied social needs and adjust the conditions of the geographical environment accordingly rather than to concentrate on the disability itself. The main aim of the study was to recognise the opinions of students with disabilities about studying at Polish higher education institutions (HEI). The study was based on the results of online interviews including standardised questions (open- and close-ended). The time scope of the study covers the years 2019 and 2021. The research has shown that some students hide their disability until it is visible. As a result, they do not receive adequate support and limit the achievement of goals that were the main motivation for studying. Measures taken to support students with different needs at HEIs must have a systemic nature and be addressed to the entire academic community, as well as to the society.